2023
DOI: 10.1126/scitranslmed.adg1485
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of neuromuscular synapses after acute and chronic denervation by inhibiting the gerozyme 15-prostaglandin dehydrogenase

Mohsen A. Bakooshli,
Yu Xin Wang,
Elena Monti
et al.

Abstract: To date, there are no approved treatments for the diminished strength and paralysis that result from the loss of peripheral nerve function due to trauma, heritable neuromuscular diseases, or aging. Here, we showed that denervation resulting from transection of the sciatic nerve triggered a marked increase in the prostaglandin-degrading enzyme 15-hydroxyprostaglandin dehydrogenase (15-PGDH) in skeletal muscle in mice, providing evidence that injury drives early expression of this aging-associated enzyme or gero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…It is generally understood that after a successful tissue regeneration process, resolution of immune response allow for the tissue to return to homeostasis (Ortega-Gomez, et al, 2013; Aurora and Olson, 2014; Julier, et al, 2017); our results suggest the role of FAPs in regulating immune resolution near the end of nerve regeneration. Furthermore, the role of prostaglandin in peripheral nerve regeneration has recently been described (Forese, et al, 2020; Bakooshli, et al, 2023); our ORA results suggested that FAPs may also be involved in regulation of prostaglandin levels during peripheral nerve regeneration.…”
Section: Resultssupporting
confidence: 69%
“…It is generally understood that after a successful tissue regeneration process, resolution of immune response allow for the tissue to return to homeostasis (Ortega-Gomez, et al, 2013; Aurora and Olson, 2014; Julier, et al, 2017); our results suggest the role of FAPs in regulating immune resolution near the end of nerve regeneration. Furthermore, the role of prostaglandin in peripheral nerve regeneration has recently been described (Forese, et al, 2020; Bakooshli, et al, 2023); our ORA results suggested that FAPs may also be involved in regulation of prostaglandin levels during peripheral nerve regeneration.…”
Section: Resultssupporting
confidence: 69%
“…VAMP-1 signal and distribution, clearly shows that both MT1 agonists speed up the recovery of presynapse with respect to mock controls. The extent of recovery was estimated by calculating the percentage of denervated, partially innervated, and innervated NMJs, as well as the NMJ occupancy, which characterizes the overlap between the presynaptic and postsynaptic morphology [62]. Results are reported in panels B, C, of Fig 3 and parallel the electrophysiological findings.…”
Section: Agonists Of Melatonin Receptor Type 1 Strongly Promote the F...mentioning
confidence: 63%